Transcript text: Simplify $\mathbf{m} \wedge(\neg \mathbf{n} \vee \mathbf{n})$ to $\mathbf{m}$
Solution
Solution Steps
Step 1: Applying the Complement Law
We are given the expression \(m \wedge (\neg n \vee n)\). Notice that \(\neg n \vee n\) matches the complement law, which states that \(a \vee \neg a = T\). Therefore, we can replace \(\neg n \vee n\) with \(T\).
So, the expression becomes \(m \wedge T\).
Step 2: Applying the Identity Law
Now we have \(m \wedge T\). This matches the identity law, which states that \(a \wedge T = a\). In our case, 'a' is 'm'. So, replacing \(m \wedge T\) with \(m\), we get our simplified expression.